Corporate Sustainability Performance: The Role Of Governance Mechanisms And Effect On Firm Value Of Listed Companies In Nigeria - Bashiru, Mahmud (2023)
The main objective of this study is to examine the influence of corporate governance mechanisms on CSP of listed companies in Nigeria and the effect of CSP on firm value. The research framework is drawn from stakeholder, agency and resource dependency theories. The sample of the study include all non-financial companies listed on the Nigerian stock exchange and secondary data from the annual reports is utilized.